Hubungan Kualitas Tidur, Tingkat Stres dan Pola Makan dengan Gula Darah Sewaktu (GDS) pada Mahasiswa Fakultas Kedokteran Universitas Islam Al–Azhar Angkatan 2022 Dan 2023 - Sentana, Dimas Arya; Utami, Sukandriani; Wulandari, Shinta; Sukamajaya, Ali (Universitas Malahayati, 2024)
ABSTRACT Hyperglycemia is a medical condition characterized by an increase in blood sugar levels that exceed normal limits, which is characteristic of several diseases, especially Diabetes Mellitus. According to West Nusa Tenggara Riskesdas data, the prevalence of DM based on doctor's diagnosis in the population aged ≥15 years was 14,825 people. To analyze the relationship between sleep quality, stress level, and diet with blood sugar level in students of Faculty of Medicine, Al-Azhar Is lamic University, batch 2022 and 2023. Observational analytic quantitative research with cross sectional study design. The research was conducted at Islamic University-Al Azhar on Thursday, January 25, 2024. The sampling technique used probability sampling, namely stratified random sampling with a sample size of 75 respondents. Data were analyzed using the Chi-Square correlation test with a significance value limit (p-value) <0.05. The results showed that the majority were 20 years old (44%), female gender (61.3%), and batch 2023 (52.0%), had normal blood sugar (88.0%), had good sleep quality (88.0%), normal-moderate stress levels (86.7%), and adequate diet (85.3%). Bivariate analysis showed that there was a relationship between sleep quality and Instantaneous Blood Sugar (p=0.000), stress level with Instantaneous Blood Sugar (p=0.000), and diet with Instantaneous Blood Sugar (p=0.000) in students of the Faculty of Medicine, Al-Azhar Islamic University class of 2022 and 2023. Conclusion: Sleep quality, stress level, and diet are associated with Instantaneous Blood Sugar in students of the Faculty of Medicine, Al-Azhar Islamic University class of 2022 and 2023. Keywords: Sleep Quality, Stress Level, Eating Patterns, and Instantaneous Blood Sugar ABSTRAK Hiperglikemia merupakan kondisi medis yang ditandai dengan peningkatan kadar gula dalam darah yang melebihi batas normal sehingga menjadi karakteristik dari beberapa penyakit terutama penyakit DM. Menurut data Riskesdas Nusa Tenggara Barat prevalensi DM berdasarkan diagnosis dokter pada penduduk usia ≥15 tahun sebanyak 14.825 jiwa. Menganalisis hubungan antara kualitas tidur, tingkat stres dan pola makan dengan Gula Darah Sewaktu pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar angkatan 2022 dan 2023. Penelitian kuantitatif analitik observasional dengan desain penelitian cross sectional study. Penelitian dilaksanakan di Universitas Islam-Al Azhar pada hari Kamis, 25 Januari 2024. Teknik pengambilan sampel menggunakan probability sampling yaitu dengan stratified random sampling dengan besar sampel 75 responden. Data dianalisis dengan uji korelasi Chi-Square dengan batas nilai signifikansi (p-value) < 0,05. Hasil penelitian menunjukkan mayoritas berusia 20 tahun (44%), jenis kelamin perempuan (61,3%), dan angkatan 2023 (52,0%), mengalami gula darah sewaktu normal (88,0%), memilki kualitas tidur baik (88,0%), tingkat stres normal-sedang (86,7%), dan pola makan yang cukup (85,3%). Analisis bivariat menunjukkan terdapat hubungan kualitas tidur dengan gula darah sewaktu (p=0,000), tingkat stres dengan gula darah sewaktu (p=0,000), dan pola makan dengan gula darah sewaktu (p=0,000) pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar angkatan 2022 dan 2023. Kualitas tidur, tingkat stres, dan pola makan berhubungan dengan Gula Darah Sewaktu (GDS) pada mahasiswa Fakultas Kedokteran Universitas Islam Al-Azhar angkatan 2022 dan 2023. Kata Kunci: Kualitas Tidur, Tingkat Stres, Pola Makan, dan Gula Darah Sewaktu (GDS)